Pengaruh Bio-Slurry Padat dan Pupuk Urea Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Yoseph Yunarso; Wardati Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This study aims to determine the effect of solid bio-slurry interaction and urea fertilizer as well as get the best dose of the plant pakcoy (Brassica rapa L.). The research has been conducted in Experimental Garden of Agriculture Faculty of Riau University, Campus Bina Widya km 12.5 Simpang Baru Village, Tampan Sub District, Pekanbaru. This research was conducted for 1 month starting from January to February 2018. This research was conducted experimentally with Factorial Random Design (FRD) which consists of 2 factors. The first factor is the provision of bio-slurry consisting of 3 levels, namely: B0 (Without administration), B1 (500 g.m-2), B2 (1000 g.m-2). The second factor was Urea fertilizer consisting of 3 levels: U0 (Without administration), U1 (10 g.m-2), U2 (20 g.m-2) The data obtained were analyzed by fingerprint and tested further by Duncan multiple range test at the 5% level.The parameters observed were plant height, leaf number, leaf area, fresh weight of plant and weight of plant feasible.The results showed that the provision of solid bio-slurry and Urea fertilizer increased plant height, leaf number, leaf area, weight fresh plant and weight is feasible for consumption of pakcoy crops Provision of 1000 g.m-2solid Bio-slurry can increase plant height, leaf number, leaf area, fresh weight of plant and weight of consumption of the plant pakcoy.Urea fertilizer 20 g.m-2can increase plant height, leaf number, leaf area, fresh weight of plant and weight of consumption worth of pakcoy plant.Supply of 1000 g.m-2solid Bio-slurry and Urea 20 g.m-2fertilizer showed better effect on high parameter, leaf number, leaf levers, fresh weight and weight is feasible consumption of pakcoy plants. Keywords: Plant pakcoy, Bio-Slurry solid, urea fertilizer